Academic Challenges for the Preterm Infant: Parent and Educator Perspectives. (1st June 2016) - Church, P; Cavanagh, A; Shah, V
Abstract: BACKGROUND: Preterm birth (PTB) is linked with academic challenges, attention deficit hyperactive disorder (ADHD) and behavioural problems. Emerging data suggest that educators lack awareness of the pre-term child's educational needs while no data exists regarding par-ents' understanding of these issues. OBJECTIVES: To explore educators' and parents' level of knowledge of the impact of PTB on academic achievement, ADHD, and behavioural problems adn identify facilitators/barriers to the use of available educational resources. DESIGN/METHODS: A combination of focus groups and survey were used to examine educators' and parents' knowledge, attitudes, and barriers to the impact of PTB on academic performance. Focus groups were conducted at the kindergarten to grade 3 levels at 4 schools by a trained facilitator using a guide. Parents of preterm infants who were seen in Neonatal Follow Up Clinic with children being 4 to 8 years of age participated. The survey included questions on parental perception of knowledge among their child's educator of outcomes of PTB, current educational placement for their child and perception of barriers and facilitators. Data were analyzed using thematic analyses or descriptive statistics. RESULTS: Educators with knowledge about PTB stated that it was largely experiential and none received formal training. Current training is focused on ADHD, Autism, or Fetal Alcohol Syndrome. In regard to facilitators/ barriers, there was no consensus on what resources would be useful (e.g. enrolling child based on the expected rather than actual date of birth if they fall in separate academic enrollment years or having knowledge that the child was preterm). Survey showed that most parents informed educators about their child's history of PTB. This disclosure increased with decreasing gestational age (GA) (92.9% for <26 weeks, 85.5% for 27-32 weeks, and 54% for >33 weeks). 54% of parents believed that their child had learning challenges and attributed this to the child's PTB. 40% believed that the school met their child's needs. One-third of parents stated that their child's eduators knew nothing of prematurity. Factors that enhanced educators' performance on assessment of knowledge were: having taught a preterm child or a child with an individualized education plan in their class, and additional qualifications of the educator. CONCLUSION: Educators and parents are unprepared to address the academic needs of preterm infants. Educators need to be trained on the outcomes of PTB and parents should be prepared to advocate for their child in the school system.